PATTERNS OF STUDENT MENTORING FROM THE CAMPUS TEACHING PROGRAM IN IMPROVING STUDENT LITERACY AT SDN 43 CAKRANEGARA - Warok, Niswatun; Syafruddin, Syafruddin; Malik, Imam; Nursaptini, Nursaptini (PROGRES PENDIDIKAN, 2024)
This research aims to find out, identify, and analyze students' literacy abilities and patterns of mentoring students from campus teaching programs to improve student literacy at SDN 43 Cakranegara. The approach used in this research is a qualitative approach with a case study method. The data collection techniques used were observation, interviews, and documentation. The data analysis technique in this research uses qualitative data analysis techniques with a data reduction process, data presentation, and conclusion. The results of this research found that students' literacy skills were at the performative level. The pattern of mentoring campus teaching program students in this research was carried out by (1) providing learning facilities through the School Literacy Movement program such as the use of reading corners, the use of word cards, letter cards, digital literacy, and traditional games; (2) supervise children's learning activities by differentiating innovation programs according to learning styles and according to reading and writing skills in low-grade students and high-grade students; and (3) supervise the use of children's learning time in a program called the School Literacy Movement by scheduling structured activities for high and low-grade students. After mentoring students who have difficulty in reading, based on the results of observations and interviews, the average low-grade students who previously did not know letters became familiar with letters and moved up the level reading level 2, namely the group of students with the level of ability to read words and sentences, while in high grades, the average was able to read fluently from those who were previously at the stage of spelling letters. Apart from observations and interviews, based on the results of the AKM post-test, the literacy rate of students increased by around 5-10%.